Diarrhoea Caused by Diffuse Metastatic Lobular Breast Cancer. (22nd May 2016) - Bakker, Sjoerd F.; Moolenaar, Willem; van Santen, Marije M.; Hendriks, Mathijs P.
Abstract : A 70-year-old woman with a history of lobular breast cancer presented to our Outpatient Clinic with diarrhoea for the past 3 years. Clinical examination and laboratory research were normal. Colonoscopy showed diffuse mild erythema and a decreased vascular pattern. Biopsies from the ascending colon, transverse colon, and descending colon showed metastases of lobular breast carcinoma. Although gastrointestinal metastases are rare in breast cancer, our case emphasizes the need for further diagnostic efforts in patients with gastrointestinal symptoms and a history of breast carcinoma.